Aging increases flexibility of postural reactive responses based on constraints imposed by a manual task - de Lima-Pardini, Andrea Cristina; Coelho, Daniel Boari; Silva, Marina Brito; Azzi, Nametala Maia; Martinelli, Alessandra Rezende; Horak, Fay Bahling; Teixeira, Luis Augusto (Frontiers in Aging Neuroscience, 2014)
This study compared the effect of stability constraints imposed by a manual task on the adaptation of postural responses between 16 healthy elderly (mean age = 71.56 years, SD = 7.38) and 16 healthy young (mean age = 22.94 years, SD = 4.82) individuals. Postural stability was perturbed through unexpected release of a load attached to the participant’s trunk while performing two versions of a voluntary task: holding a tray with a cylinder placed with its flat side down (low constraint) or with its rolling round side down (high constraint). Low and high constraint tasks were performed in alternate blocks of trials. Results showed that young participants adapted muscular activation and kinematics of postural responses in association with previous experience with the first block of manual task constraint, whereas the elderly modulated postural responses based on the current manual constraint. This study provides evidence flexibility of postural strategies in elderly to deal with constraints imposed by a manual task.